Financing Development: Private Capital Mobilization and Institutional Investors - Georg Inderst (ZBW - Leibniz Information Centre for Economics, 2021)
This report discusses key issues around the mobilization of private capital for development. Investment requirements are huge, especially for infrastructure, climate and other SDG-related investments. External finance for developing countries stagnated in the years before the pandemic, followed by a major setback in 2020/2021. The focus is in particular on institutional investors, whose exposure to less-developed countries is still very low, even more so in unlisted assets and projects. There is a potential for progress as asset owners seek new diversification opportunities in growth markets. The main burden is on governments to create favourable business conditions for investable long-term assets. Policy makers, development finance institutions and investors should utilize the full spectrum of investment vehicles - commercial, impact and blended finance.
Keywords: F21; F3; G15; G18; G2; H54; H57; J32; L9; M14; O16; O18; O19; Q01; Q5; 330; development finance; private capital; institutional investors; SDG investing; emerging markets; multilateral development banks; blended finance; infrastructure investment; development finance institutions; asset owners; impact investment